Pola Asuh Orang Tua dalam Membentuk Akhlak Sesama Manusia pada Anak Keluarga Nelayan Kampung Pasir Ganting Kabupaten Pesisir Selatan - Utama, Meiji Colna Putri; Yetti, Murni (MASALIQ, 2023)
This study aims to find out how parents' upbringing in shaping the morals of fellow humans in the children of fishermen families in Pasir Ganting Village, Pesisir Selatan Regency and also to find out what factors influence parenting patterns in forming the morals of fellow humans in children of fishermen families in Pasir Ganting Village. South Coastal District. The subject of this research is parenting style. Informants in this study were parents and children aged 8-13 years, and the method chosen in this study was descriptive qualitative method. The results of this study are that the parenting style used by parents in the Pasir Ganting fishing village is mostly authoritarian parenting and democratic parenting. The most dominant factor that can influence parenting in shaping the morals of fellow human beings in the children of the Pasir Ganting fishing village is the environmental factor where they live, and there are also other factors that can influence parenting patterns, namely the personality factor of the parents.